2008
DOI: 10.1037/a0012762
|View full text |Cite
|
Sign up to set email alerts
|

Understanding motivation for exercise: A self-determination theory perspective.

Abstract: Understanding the factors that motivate health-enhancing physical activity has considerable merit given the role of this lifestyle behaviour in combating disease and promoting quality of life. The purpose of this article is to provide a broad overview of research investigating participation issues in exercise from the perspective of self-determination theory (SDT; Deci & Ryan, 2002). Evidence informing the application of SDT to the study of motivational issues in exercise is reviewed around three central quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 49 publications
6
130
0
14
Order By: Relevance
“…40 Unlike introjection, ID regulation is argued to be important for persisting in behaviors that are valued but that are not always inherently pleasurable, such as exercise. 44,88 Most importantly for the present study, previous literature has shown ID regulation for physical activity to be related to enduring indicators of well-being such as physical self-worth and life satisfaction. 35,89 In our sample of women, situational ID regulation was not significantly related to post-activity positive affect.…”
Section: Articlementioning
confidence: 87%
“…40 Unlike introjection, ID regulation is argued to be important for persisting in behaviors that are valued but that are not always inherently pleasurable, such as exercise. 44,88 Most importantly for the present study, previous literature has shown ID regulation for physical activity to be related to enduring indicators of well-being such as physical self-worth and life satisfaction. 35,89 In our sample of women, situational ID regulation was not significantly related to post-activity positive affect.…”
Section: Articlementioning
confidence: 87%
“…However, there has been a recent increase in use of self-determination theory in the physical activity domain. Wilson et al [14] reviewed evidence that social contexts may be correlated with psychological need satisfaction and that within physical activity contexts, the environment may promote or inhibit need satisfaction. Both cross-sectional [12] and longitudinal studies [15,16] illustrate the effect of psychological need satisfaction on physical activity.…”
Section: Introductionmentioning
confidence: 98%
“…A Teoria da Autodeterminação (TAD) vem sendo utilizada em estudos (Wilson, Mack, & Grattan, 2008, Wilson, Rodgers, Blanchard, & Gessel, 2003 para explicar os diferentes fatores motivacionais que levam a população a iniciar, persistir e/ou abandonar a prática de atividades físico-esportivas. A motivação, nessa teoria, é compreendida dentro de um continuum e pode variar desde a sua forma mais autônoma (autodeterminada), até aquela controlada por aspectos externos (Edmunds, Ntoumanis, & Duda, 2006), considerando que as regulações externas manifestam-se de diferentes formas (Ryan & Deci, 2000).…”
Section: Introductionunclassified